Developing Novel Chemotherapeutics: A Structure-Activity Study of Anandamide Analogs and their Cytotoxic Profiles - Morris, Andrew (East Carolina University, 2020)
Many epithelial cancers have been shown to overexpress the enzyme cyclooxygenase-2 (COX-2), an enzyme responsible for both the metabolism of arachidonic acid (AA) to prostaglandins and arachidonoyl ethanolamine (AEA) to prostaglandin-ethanolamides (prostamides). AEA has demonstrated cytotoxicity in COX-2 overexpressing cancers via its metabolism to the novel J-series prostamide, 15d-PMJ2. Using what is known about how AEA induces cell death, derivatives of AEA were synthesized to investigate COX-2 metabolism, PGDS metabolism, FAAH degradation resistance, and the inherent cytotoxicity of their J-series prostaglandin analogs. A structure-activity relationship study was conducted with ten AEA derivatives to determine what modifications to the ethanolamide moiety improve anti-cancer activity in COX-2 overexpressing JWF2 tumorigenic keratinocytes and HCA-7 colorectal cancer cells. Important cytotoxic characteristics of AEA and AEA analogs were identified from the SAR study. Hydrogen bond accepting or donating ability seems to be the most important characteristic retained in cytotoxic AEA analogs. Distance between the amide bond and terminal hydroxyl moiety seems to be important, but no trend as to whether a shorter or longer carbon chain is apparent. Addition of an aryl group does not interfere with cytotoxicity and in fact improves it as long as a terminal hydroxyl group is retained. Two derivatives which displayed cytotoxicity similar to or greater than that of AEA, NAGly and arvanil, were selected for further studies exploring their cytotoxic and metabolic profiles. Arvanil (LC50 = 6.03 [micro]M) demonstrated greater cytotoxicity than NAGly (LC50 = 9.54 [micro]M) and our positive control AEA (LC50 = 9.39 [micro]M). Metabolism by COX-2 and PGDS to D-series and J-series prostaglandin analogs were responsible for arvanil's apoptotic anti-cancer activity. The novel J-series prostamide analog, 15d-PMJ2-arvanil, was identified for the first time as well as another metabolite, possibly an A-series prostamide analog, with identical mass-to-charge ratios and fragmentation patterns in the mass spectrum. These molecules will be synthesized, and their anti-cancer activity investigated in future studies. Collectively, these results suggest that structural modification of the ethanolamide moiety of AEA provides a means for improving both the selectivity and cytotoxicity of prodrugs resulting in formation of novel J-series prostamides.
Keywords: Endocannabinoid; Skin Cancer; Colorectal Cancer; Chemotherapeutic; Prostaglandin; Cancer--Research; Cannabinoids; Drugs--Research; Organic compounds--Synthesis